Human dignity and digital minimum vital: Internet access as a fundamental right - Caldera Ynfante, Jesús E.; Rosell Aiquel, Rafael (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Human dignity, a normative category developed by the Colombian Constitutional Court, is seen from "humanist constitutionalism", due to its functionality for the configuration of the fundamental human right of access to the Internet that translates into a digital vital minimum of the human person, emphasizing in the inclusion of the poor and vulnerable affected by digital inequality. A complex fundamental hyperright that obliges the State to guarantee the human rights of their essential core and formulate public policies for their effective satisfaction inherent in the realization of the valuable life project of the person and their effective functioning in society.